離乳後のクロホスファミドの急性適応が成体期のストレス反応性および海馬神経幹・前駆細胞の増殖能に与える影響 - 米山, 雅紀; 尾中, 勇祐; 山口, 太郎 (日本薬理学会年会要旨集, 2022)
Chemotherapy for childhood cancer can cause late-appearing side effects in survivors that affect multiple organs, including the brain. Cyclophosphamide is used in childhood cancer and has the blood brain barrier permeability. The present study aims to reveal whether an acute treatment with cyclophosphamide after weaning affects the brain function and hippocampal neurogenesis in the adult mouse. Cyclophosphamide were intraperitoneally once injected to 3 weeks old male ddY mice. Five weeks after injection, restraint stress loading or the behavioral test battery was performed. After the test battery, mice were received 2 consecutive injections of 5-bromo-2′-deoxyuridine (BrdU) with a 12-h interval. BrdU positive cells in the hippocampal dentate gyrus were counted after immunostaining for BrdU. Treatment with cyclophosphamide had the ability to enhance restraint stress-induced increase of plasma corticosterone, and decrease the number of BrdU-positive cells in the dentate gyrus 5 weeks afterward. However, cyclophosphamide failed to change emotional and cognitive functions. These data suggest that the acute treatment with cyclophosphamide in post-weaning exhibits prolonged changes in stress response and the suppressive effect on hippocampal neurogenesis.